Integration of Cash Waqf in The Halal Value Chain Ecosystem: A Strategy to Strengthen The Competitiveness of Halal Products - Nissa, Izzun Khoirun; Safitri, Yuni; Mohammed Hasan, Baidar Mohammed (Likuid Jurnal Ekonomi Industri Halal, 2025)
Cash waqf is an Islamic social finance instrument that has great potential in supporting sustainable economic development, especially in the halal value chain ecosystem. This study aims to analyze the integration strategy of cash waqf in strengthening the competitiveness of halal products based on Islamic economic principles. Through a qualitative approach with literature study and conceptual analysis, this study finds that the integration of cash waqf can be a stable and inclusive alternative funding source for strategic sectors in the halal value chain, such as halal agriculture, food and beverage industry, pharmaceuticals, cosmetics, and Islamic logistics. Waqf money that is managed professionally and transparently can be used to support working capital financing, capacity building for halal MSMEs, and halal infrastructure development, thus encouraging efficiency, innovation, and standardization of halal products. In addition, this integration also strengthens aspects of social justice and wealth distribution through a sustainable empowerment model. This research recommends synergy between nazir institutions, halal industry, Islamic financial authorities, and the government in building a policy framework that allows cash waqf management to be integrated with the halal value chain.